1996
DOI: 10.1097/00001648-199607000-00007
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of Maternal Drinking before Conception and in Early Pregnancy on Infant Birthweight

Abstract: We examined the association of maternal drinking before and during early pregnancy on infant birthweight, using data collected from a population-based cohort in Avon Country, England. Participants completed several self-administered questionnaires during their index pregnancy. Our analysis included 10,539 women who provided drinking data and delivered a liveborn singleton child. Infants born to women who reported drinking one to two drinks daily with at least one binge, or three or more drinks daily with or wi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
52
0
2

Year Published

1998
1998
2012
2012

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 85 publications
(58 citation statements)
references
References 27 publications
4
52
0
2
Order By: Relevance
“…No effect was seen in infants born to women who drank weekly in early pregnancy, less than weekly or not at all (Passaro et al, 1996). Shu et al (1995) found that alcohol consumption in the first trimester (average four drinks per week) was associated with a 155 g reduction in fetal weight, even after adjustment for number of cigarettes smoked.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…No effect was seen in infants born to women who drank weekly in early pregnancy, less than weekly or not at all (Passaro et al, 1996). Shu et al (1995) found that alcohol consumption in the first trimester (average four drinks per week) was associated with a 155 g reduction in fetal weight, even after adjustment for number of cigarettes smoked.…”
Section: Discussionmentioning
confidence: 98%
“…However, despite its clinical significance, the effect of moderate alcohol drinking in pregnancy on the risk of small for gestational age (SGA) birth is controversial (Day et al, 1989;Shu et al, 1995;Windham et al, 1995;Passaro et al, 1996).…”
Section: Introductionmentioning
confidence: 99%
“…The potential negative effect of alcohol drinking in pregnancy on birth weight and preterm delivery is controversial (Die et al, 1989;Shu et al, 1995;Windham et al, 1995;Passaro et al, 1996;Makarechian et al, 1998). For example, a recent cohort study based on postal questionnaires conducted in Denmark (Kesmodel et al, 2000) has suggested that heavy alcohol drinking during the first 30 weeks of gestation increases the risk of preterm births about three-fold.…”
Section: Introductionmentioning
confidence: 99%
“…In the interpretation of the existing epidemiological studies regarding the harmful effects of binge drinking, our conclusion regarding the decline in the accuracy of the reported information on binge drinking as the recall period increases is important. The major part of the existing studies has collected information on binge drinking in the second half of pregnancy or subsequent to birth (Tolo and Little, 1993;Olsen, 1994;Pascoe et al, 1995;Passaro et al, 1996;Iyasu et al, 2002;Whitehead and Lipscomb, 2003) and therefore the information on binge drinking is most likely underestimated. Due to this underestimation, actual exposed women may be categorized as non-exposed and the estimates could probably be biased towards the null-value.…”
Section: Discussionmentioning
confidence: 99%
“…If such periods exist, it may explain why previous studies have failed to find any association between binge drinking and birth weight, length at birth, head circumference, gestational age, Apgar score and malformations. (Tolo and Little, 1993;Olsen and Tuntiseranee, 1995;Passaro et al, 1996;Kesmodel, 2001;Whitehead and Lipscomb, 2003).…”
Section: Introductionmentioning
confidence: 99%